Board Characteristics and Accounting Quality of Chinese High-technology Listed Firms - Lin, Jingjing (2019)
The objective of the study was to examine the correlation between board characteristics and accounting quality in Chinese high-technology listed firms. The study employed panel data analysis and the sample consisted of 527 firms over a period of 5 years from 2014 to 2018. The accounting quality was the dependent variable, which was quantified by the earnings management and value relevance respectively. The earnings management was measured by the discretionary accruals of the firms. The value relevance represented the relation of the market price per share and accounting figures which are book value per share and earnings per share of the firms. Board characteristics acted as the independent variables which are the board size, board independence, board meetings and CEO duality respectively. The study also included three control variables: firm size, firm growth and leverage. The findings indicated the impacts of the board characteristics were different. Board size and firm size were negatively correlated with earnings management, while firm growth and leverage had significant positive impacts on earnings management. Board size, CEO duality, firm size and firm growth were negatively related to the value relevance of the book value, but board meetings and leverage had positive effects. Board independence, board meetings, firm size and leverage were negatively associated with the value relevance of the earnings per share. The main contribution of the study was that the topic had not covered in Chinese high-technology firms, which may provide some advice for the firms on development. Further studies might use qualitative methods to conduct studies. More independent variables could be considered to explain the correlation. The longer time horizon could be estimated as well. The measurements of variables may be employed in the future.